579. Epidemiological Data Differences between Gel-purified vs. DNA-purified Oral Polio Vaccine in environmental samples. (15th December 2022) - Carrington, Yuan J; Zhou, Frank; Walter, Katharine; Leary, Sean; Altamirano, Jonathan; Maldonado, Yvonne A
Abstract: Background: As wild poliovirus is eradicated, preventing circulation of vaccine-derived poliovirus is top priority. Our lab developed real-time multiplex PCR assays and deep sequencing methodology to detect and characterize OPV strains from stool samples. The method requires gel purification of PCR product created from viral RNA in stool samples. However, the process filters out a significant portion of samples. Here, we compare gel- vs. DNA- purification and sample retainment for downstream analysis. Methods: 554 stool samples qPCR positive for at least one OPV serotype from a previous study were used. There are 268 serotype 1 (S1) isolates, 405 serotype 2 (S2) isolates, and 318 serotype 3 (S3) isolates. PCR amplicons created from viral RNA ran through a 0.08% agarose gel to identity presence of the ∼3.5kb amplicon of interest. PCR amplicons then underwent either a gel-purification spin column kit or a DNA purification spin column kit. Samples with DNA concentration >10ng/uL in the elution product is required for NGS. Purification Methods Flowchart Graph 1: Gel-purification, DNA-purification, and suggested purification workflow charts Results: Comparing 168 S2 samples gel vs. DNA-purified, of 90 bands identified with both protocols, 100% of DNA-purified samples and 35.6% of the gel-purified samples had DNA concentration >10ng/ul. 41.3% of banded samples with < =34CT had >10ng/ul for gel-purified samples vs. 100% for DNA-purified samples. Of 43 pediatric participants, prior OPV and IPV did not impact proportion of number of individuals with viable samples for NGS (16/31 (51.6%) vs 25/43 (58.1%) respectively). Among samples processed via gel purification, the median number of samples per positive participant dropped from 2 (IQR=1-3) to 1 (IQR=1-1). From the same set of samples, gel purification reduced the number of OPV vaccinated children 38 (82.6%), their household contacts 2 (4.3%), and community contacts 6 (13%) to 21 (80.7%) OPV vaccinated children, 1 (3.8%) household contacts, and 4 (15.3%) community contacts. Table 1: Purification outcome of 168 S2 unique-participant-day (UPD) samples via gel-purification and DNA-purification Graph 2: Demographic information of patient sample loss form the gel-purification process on 168 S2 samples via gel-purification workflow 2a. Sample collection across different days for 90 unique-participant-day (UPD) samples pre gel-purification vs 32 UPD samples post gel-purification. 2b. OPV and IPV does spread per each 43 pediatric unique-participant (UP) from the 90 UPD samples pre gel-purification vs 25 pediatric UP from the 32 UPD post gel-purification. 2c. Vaccination status (OPV vaccinated child, household contact, unvaccinated community contact) of each 43 unique-participant (UP) from the 90UPD samples pre gel-purification vs 25 UP from the 32 UPD post gel-purification. 2d. Number of samples collected per UP fron the 90 UPD samples pre gel-purification vs 32 UPD samples post gel-purification. Graph 3: Demographic information of patient sample loss form the gel-purification process on 168 S2 samples via suggested purification workflow 2a. Sample collection across different days for 75 unique-participant-day (UPD) samples pre gel-purification vs 31 UPD samples post gel-purification. 2b. OPV and IPV does spread per each 38 pediatric unique-participant (UP) from the 75 UPD samples pre gel-purification vs 24 pediatric UP from the 31 UPD post gel-purification. 2c. Vaccination status (OPV vaccinated child, household contact, unvaccinated community contact) of each 41 unique-participant (UP) from the 75UPD samples pre gel-purification vs 25 UP from the 31 UPD post gel-purification. 2d. Number of samples collected per UP fron the 75 UPD samples pre gel-purification vs 31 UPD samples post gel-purification. Conclusion: Conclusions : Gel-purification causes a reduction in sample numbers and variation, causing an incomplete data set and data misrepresentation for downstream analysis, particularly a reduction of samples for within host variation analysis. DNA purification of banded samples with < =34CT may be most optimal for NGS. Analysis of all isolates are in process. Disclosures: Yvonne A. Maldonado, MD, Pfizer: Grant/Research Support|Pfizer: Member, DSMB, Pfizer Meningococcal Vaccine clinical trial.